Logika monetarystyczno-liberalna w badaniach rzeczywistości gospodarczej - Noga, Marian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The autor presents systemic efficiency as completed to classical efficiency in the light of neoclassical economy. Monetary and liberal logic have to base both on individual methodology and on holistic methodology. If we take together individual and holistic methodology in economic research, we receive result, as predictive conclusions (hypothesis, forecast, model). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 377-385